Pencarian Hukum Menurut Ushul Fiqih - Muttaqin, M.Imamul; Farikha, Naila Azka; Mauludya, Dita; Ramadhani, Diva Adila Aulya; Kartika, Adhisti Malla (Jurnal Pendidikan Islam, 2024)
His article aims to examine how customs are the source of fiqh law. Ushul fiqh is a study within the framework of Islamic law research methods. It deals with social reality and provides a social framework for phenomena that will occur now and in the future. The important role of ushul fiqih as the guardian of shari'a or Islamic law whose foundations by the Prophet Muhammad (saw) has been demonstrated fifteen centuries ago. Ushul fiqh has the characteristics of Islamic sharia law logic that is different from other laws. The customary law is interpreted according to several opinions of jurists. The customary law is interpreted according to several opinions of jurists. Also regarding Saddu al-Dzariah, where there are differences of opinion regarding the determination of the law whether this law should be formed or not. As for Madzhab shahabi and Syar'u Man Qablana which will be discussed in this article. From these three sources, the formation of Islamic law is still based on the Qur'an and Hadith which are the core of all Islamic law.